2010
DOI: 10.1088/1742-6596/224/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Electrode models under shape deformation in Electrical Impedance Tomography

Abstract: Abstract. Electrical Impedance Tomography (EIT) applies current and measures the resulting voltage on the surface of a target. In biomedical applications, this current is applied, and voltage is measured through electrodes attached to the surface. Electrode models represent these connections in the reconstruction, but changes in the contact impedance or boundary relative to the electrode area can introduce artifacts. Using difference imaging, the effects of boundary deformation and contact impedance variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…There are several electrode models in the literature (e.g. shunt, complete, [5], [13], [2]) in which different electrical boundary conditions are applied together with certain assumptions about the electrode-surface interaction. In realistic settings, and in this study, the complete electrode model is often used since it also includes realistic contact impedances ([5]).…”
Section: Introductionmentioning
confidence: 99%
“…There are several electrode models in the literature (e.g. shunt, complete, [5], [13], [2]) in which different electrical boundary conditions are applied together with certain assumptions about the electrode-surface interaction. In realistic settings, and in this study, the complete electrode model is often used since it also includes realistic contact impedances ([5]).…”
Section: Introductionmentioning
confidence: 99%
“…An efficient and accurate method for calculating the electrode position Jacobian on a 2.5-D resistivity model was developed. This work is motivated by developments in Boyle & Adler (2010); Boyle (2010) for 2-D electrode movement, and Boyle et al (2014); Boyle (2016); Boyle & Adler (2016) where this data set and preliminary results were presented. A 2-D cross-sectional Finite Element Method (FEM) model of the local slope topology was built, with electrodes modelled using the Complete Electrode Model (CEM) (Somersalo et al 1992;Rücker & Günther 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are different kinds of BCs used in the EIT forward problems, including the Gap Model (Boyle and Adler 2010), Shunt Electrode Model (Boyle and Adler 2010) and Complete Electrode Model (CEM) (Boyle and Adler 2010, Cheng et al 1989, Somersalo et al 1992, Vauhkonen et al 1999. The CEM constrains the electrical currents flowing on the electrode surfaces and on the boundary of the imaging volume.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the CEM can match experimental results with a very high precision up to 0.1 % (Somersalo et al 1992). To reconstruct accurate images from in vivo data an accurate electrode model is usually required, and thus, the CEM is generally preferred (Boyle and Adler 2010). The accuracy of CEM solutions depends on accurate measurements or estimations of the contact impedance.…”
Section: Introductionmentioning
confidence: 99%